Digital signal processing : fundamentals and applications - Tan, Li; Jiang, Jean. (2013)
"Bridging the gap between theory and application, this text covers all the main areas of modern DSP. Principles, applications, and hardware implementation issues are presented, and a wealth of worked examples and end of chapter exercises provide the opportunity for self-learning. Throughout the book emphasis is placed on applications to signal, image, and video processing, and real time implementation of DSP algorithms using DSP processors is highlighted."--Back Cover.
Keywords: Signal processing -- Digital techniques